MEDICAL SIGNS MEANINGS IN TERMOREX IN 1993 - Lestari, Indri Julianti; Ernawati, Ernawati (Universitas Islam Negeri Sunan Gunung Djati, 2024)
This study aimed to analyze medical signs contained in the Termorex advertisement published in 1993 on television. It used the semiotic theory of Charles Sanders Pierce in Vera (2014). It applied a qualitative descriptive research method. The data were all of signs contained in the 1993 Termorex advertisement. The data were in the form of audiovisual signs which were then divided into sign, object, and interpretant. Advertising on television has advantages: wide reach, selectivity and flexibility, centre of attention, creativity and effect, prestige, time, and disadvantages: expensive costs and limited information. The study revealed that the 1993 Termorex advertisement contains unique meanings. Colours become particular signs in the study. The object shows color changes between red, yellow, and green of the text and thermometer. The meaning of color placement on the identification of the effect of fever-reducing drugs on thermorex after the administration. Red color identifies of high fever with the number on the thermometer more than 37 degrees Celsius, yellow for drop or decrease the temperature, green same as yellow but more drop or decrease to normal. The meaning of healthy in the product slogan of Konimex that represents their product. In summary, the advertisement contains medical signs meanings.Keyword: medical sign, meaning, semiotics, termorex, advertisement